2014
DOI: 10.1177/0148607113520433
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Experimental Study on the Effect of Arginine, Glutamine, and β‐Hydroxy β‐Methylbutyrate on Secondary Wound Healing

Abstract: Diet supplemented with arginine, glutamine, and β-hydroxy β-methylbutyrate is not beneficial in enhancing secondary healing of open wounds in rats. Further research regarding this topic is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…A recent experimental research by the authors of the present study revealed no benefit of the supplementation of this amino acid mixture on the secondary healing of experimental wounds in otherwise healthy rats 7 . In the mentioned study, however, the wounds were acute, and the subjects had no metabolic impairments, unlike the patients in the clinical trials that revealed benefits of the supplement in the closure of diabetic ulcers.…”
Section: Introductioncontrasting
confidence: 60%
See 1 more Smart Citation
“…A recent experimental research by the authors of the present study revealed no benefit of the supplementation of this amino acid mixture on the secondary healing of experimental wounds in otherwise healthy rats 7 . In the mentioned study, however, the wounds were acute, and the subjects had no metabolic impairments, unlike the patients in the clinical trials that revealed benefits of the supplement in the closure of diabetic ulcers.…”
Section: Introductioncontrasting
confidence: 60%
“…The difference between the 2 groups in wound sizes was significant beginning on the 10th day and still apparent on the 14th day. In a previous trial by the authors of this article, it was demonstrated that this mixture of amino acids was not effective in accelerating the healing of acute experimental nonischemic wounds 7 . This may suggest that the enhancement in the treatment group in the present study may rather be attributed to the efficacy of this amino acid combination in wound healing only in the presence of a factor that impairs wound healing, such as ischemia.…”
Section: Discussionmentioning
confidence: 52%
“…It is postulated that this might occur via a metabolic intermediary, P5C (35). Reports have demonstrated the benefit of glutamine supplementation alone on wound collagen synthesis and accumulation in primary or secondary (36) wounds. Specifically, a study of air leak pressures after deliberate pulmonary laceration in a group of Wistar albino rats indicated that rats receiving glutamine supplementation had higher air leak pressures than control animals, and that these animals also had higher levels of immature collagen, as demonstrated by histopathology (37).…”
Section: Clinical and Preclinical Data Examining Nutrient Supplementamentioning
confidence: 99%
“…Hydroxyproline content measures collagen turnover throughout the wound-healing process and assesses wound-healing therapy quality 42 , 44 , 45 . The hydroxyproline concentration in the 10% Mattan tailam nanogel treated groups was significantly greater than in the standard formulation and Nitrofurazone groups.…”
Section: Discussionmentioning
confidence: 99%